Clinical and diagnostic imaging outcomes of mandibular fracture management in 109 cats - Evenhuis, Janny V.; Vincek, Anna; Goldschmidt, Stephanie; Soltero-Rivera, Maria; Nguyen, Mindy A.; Arzi, Boaz (Frontiers in Veterinary Science, 2025)
IntroductionMandibular injuries are a common occurrence in cats that are presented for maxillofacial trauma. Timely assessment and treatment of these injuries directly impacts a cat’s return to function.MethodsA retrospective study was performed on a population of 109 cats that were presented for evaluation and treatment of mandibular trauma. Medical records and diagnostic imaging were reviewed to determine mandibular fracture location, morphology, and treatment. Follow-up data were obtained from repeat clinical examination and diagnostic imaging.ResultsThe most commonly injured anatomical locations were the mandibular symphysis (55.0%), the condylar process of the mandible (49.5%) and mid ramus (48.6%). More severe pre-operative fracture displacement was associated with a poor healing outcome in the mid ramus and coronoid process regions. The group of cats treated with open reduction and internal fixation (ORIF) had a significantly higher percentage of cats showing adequate healing (P = 0.0247) compared to the group of cats treated with maxillomandibular fixation (MMF). Cats treated with ORIF also had lower prevalence of persistent malocclusion (9.1%) when compared to cats treated with MMF (53.9%) (P = 0.0138, respectively). Placement of an esophageal feeding tube did not have a statistically significant impact on weight change in patients post-operatively (P = 0.0973). Patient survival was high at 94.5%.DiscussionHigh patient survival indicates that cats that were diagnosed and treated for mandibular trauma often have a good prognosis. Pre-operative fracture displacement may influence healing in select regions of the mandible. Fractures treated with ORIF had a higher rate of adequate bone healing when compared with fractures treated with MMF.